The Effect of Quality of Financial Statements on Investment Efficiency MSMEs in Sumedang Regency - Fanji Farman (LPPM Universitas Sebelas April, 2023)
Investment efficiency is a project that is carried out based on all investment activities or activities that are in accordance with the company's objectives. Financial reports are one of the factors that influence investment activities. With good quality financial reports, information asymmetry can be reduced so that investment activities can run efficiently. This research aims to find out how financial reporting accuracy influences investment performance. Information from completed questionnaires was used in this investigation. Although there are still errors in company financial reports, which have a significant impact on the quality of their financial reports, research findings show that the accuracy of financial reports does not change the efficiency of investments made by investors